MOLECULAR DYNAMICS SIMULATION OF UO2: AN ALTERNATIVE RIGID ION MODEL POTENTIAL - Gunay, S. D.; Akdere, U.; Kavanoz, H. B.; Tasseven, C. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2011)
A semi-empirical effective interionic potential model has been parameterized to investigate UO2 by molecular dynamics simulation technique. The simulations were performed in the constant pressure temperature ensemble between 300 K 3200 K at 100 K intervals. The pair distribution functions and coordination numbers signal the onset of structural changes at temperatures in accord with the Bredig transition and melting. The oxygen ion diffusion coefficients calculated from the mean square displacements markedly increase the liquid like value at T > 2100 K. The transition to the superionic state and Melting are well reproduced within the limitations of a rigid ion potential.
Keywords: Uranium dioxide; molecular dynamics simulation; Bredig transition; ionic transport; INTERATOMIC POTENTIALS; SELF-DIFFUSION; URANIUM; MOTION; Physics